Role of KCNB1 in the prognosis of gliomas and autophagy modulation - Hao-Yuan Wang (Nature Portfolio, 2017)
Abstract Increasing evidence suggests that ion channel genes play an important role in the progression of gliomas. However, the mechanisms by which ion channel genes influence the progression of glioma are not fully understood. We identified KCNB1 as a novel ion gene, associated with malignant progression and favorable overall survival (OS) and progression-free survival (PFS) in glioma patients from three datasets (CGGA, GSE16011 and REMBRANDT). Moreover, we characterized a novel function of autophagy induction accompanied by increased apoptosis and reduced proliferation and invasion of glioma cells for KCNB1. KEGG pathway analysis and in vitro studies suggested that the ERK pathway is involved in KCNB1-mediated regulation of autophagy, which was confirmed by inhibition of KCNB1-induced autophagy by using a selective ERK1/2 inhibitor (U0126) or siERK1/2. In vivo studies showed that KCNB1 induced autophagy while inhibiting tumor growth and increasing survival. Overall, our studies define KCNB1 as a novel prognostic factor for gliomas that exerts its tumor suppressive function through autophagy induction.